Drone model classification using convolutional neural network trained on synthetic data - Wisniewski, Mariusz; Rana, Zeeshan A.; Petrunin, Ivan (MDPI, 2022)
We present a convolutional neural network (CNN) that identifies drone models in real-life videos. The neural network is trained on synthetic images and tested on a real-life dataset of drone videos. To create the training and validation datasets, we show a method of generating synthetic drone images. Domain randomization is used to vary the simulation parameters such as model textures, background images, and orientation. Three common drone models are classified: DJI Phantom, DJI Mavic, and DJI Inspire. To test the performance of the neural network model, Anti-UAV, a real-life dataset of flying drones is used. The proposed method reduces the time-cost associated with manually labelling drones, and we prove that it is transferable to real-life videos. The CNN achieves an overall accuracy of 92.4%, a precision of 88.8%, a recall of 88.6%, and an f1 score of 88.7% when tested on the real-life dataset.
Keywords: unmanned aerial vehicles; drones; airport security; convolutional neural network; synthetic images; synthetic data; domain randomization; drone detection; drone classification; drone identification; artificial intelligence